2008
DOI: 10.1111/j.1365-2028.2007.00889.x
|View full text |Cite
|
Sign up to set email alerts
|

Morphological criteria to identify faecal pellets of sympatric ungulates in West African savanna and estimates of associated error

Abstract: Indirect surveys may prove to be useful tools in complementing classical direct counts when monitoring ungulate populations and may also promote better understanding of the precise structure and functioning of the rich ungulate communities of African savannas. However, the identification of faecal pellets can be difficult where several sympatric species occur. This study develops simple field criteria for distinguishing between pellets among ten sympatric West African ungulates. A discriminant analysis was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
1
5
1
Order By: Relevance
“…Our results contradict the idea that diet has a strong influence on scat shape and size (Chame 2003) and the observation by Hibert et al (2008) that captive samples show important differences from wild African ungulates. However, these characteristics have only now been tested directly on species of Neotropical ungulates, so drawing definitive conclusions about how much influence diet may have is premature.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results contradict the idea that diet has a strong influence on scat shape and size (Chame 2003) and the observation by Hibert et al (2008) that captive samples show important differences from wild African ungulates. However, these characteristics have only now been tested directly on species of Neotropical ungulates, so drawing definitive conclusions about how much influence diet may have is premature.…”
Section: Discussioncontrasting
confidence: 99%
“…Despite this, these error rates are similar to those reported by Bowkett et al (2009), using dung morphology to differentiate antelope species in the Udzungwa Mountains of Tanzania. Hibert et al (2008) also experienced difficulty discriminating dung pellets of some sympatric antelope species from West African savannas; four out of ten species analyzed could not be distinguished by morphological measurements. Our results illustrate the importance of incorporating molecular methods into faecal-count studies, especially to aid species identification.…”
Section: Species Identificationmentioning
confidence: 97%
“…Methodologies based on faecal counts are commonly used, though there are many possible errors associated with these methods (Neff 1968) such as variable defecation rates, unknown decaying times and difficulty in identifying pellets of sympatric species (van Vliet et al 2008a, b). Discriminant analysis of morphometric measurements of pellets from ten sympatric West African ungulates has demonstrated that only six species could be correctly identified in the field (Hibert et al 2008). The reliability of pellet count methodologies can be improved by association with other techniques, such as direct observation, radio-tracking and molecular approaches.…”
Section: Introductionmentioning
confidence: 98%
“…Fecal samples were collected during surveys for subsequent DNA analysis. Pellet size varies among age class and sex (Murphy et al, 2003;Wehausen et al, 2004;Hibert et al, 2008;McCann et al, 2008) therefore, we avoided resampling the same individual by collecting different sized pellets at discrete water features within a population. In total, we collected 110 samples from 13 sampled populations (Fig.…”
Section: Sample Collection and Molecular Methodsmentioning
confidence: 99%